Effect of thermopriming and alpha-tocopherol spray in Triticum aestivum L. under induced drought stress : a future perspective of climate change in the region - Shakir, Ubaid Ullah; Ullah, Sami; Khan, Muhammad Nauman; Ali, Sajjad; Ali, Usman; Zaman, Akhtar; Sarah Abdul Razak,; Ozdemir, Fethi Ahmet (Penerbit Universiti Kebangsaan Malaysia, 2022)
Because of global warming and decreased river flows, all of Pakistan’s provinces, especially large parts of Sind and Baluchistan, have been experiencing water shortages for decades. Based on such climatic changes several management techniques have been recommended to cope through drought stress. This study is focused on the assumption that seed soaking of Triticum aestivum L. at low (4 °C) and high (80 °C) temperature (thermopriming) with exogenous spray of alpha-Tocopherol (150 mol/L) will increase seedling formation and crop production through drought stress of 5 and 10 days recommended to persuade resistivity in test species. This study also describes resistance mechanism of drought both in physiological and biochemical activities. Results concluded that chlorophyll a & b, carotenoids, sugar, protein and proline (μmg/g) contents were detected maximum in case of T1 (control) and T5 (5 days drought + 4 °C + α-Tocopherol) enhancing growth and osmolytes component in plant whereas; antioxidant enzymes bitterly respond under induced high drought stress and growth regulator at p≤0.05. The study showed the degree of resistance to various drought stressors best suited in agricultural country (Pakistan) signifying successful demonstration of priming method with the application of α-Tocopherol as growth regulator will help agricultural industries improve seed quality and germination rate.